PENGENALAN PROFESI APOTEKER SERTA EDUKASI DAGUSIBU OBAT YANG BENAR DI MAS Al-MANAR MEDAN JOHOR - Sulasmi Sulasmi Sulasmi; Bunga Rimta Barus; Nada Amirah; Muhammad Rifqi Azhary; Muhraza Siddiq (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Pharmacist is a profession to devote itself to humanity in the field of health, requires high knowledge obtained from formal education, its primary orientation must be aimed at the benefit of society. Low public curiosity about the correct use of drugs is very dangerous, therefore it is important to educate the public so that knowledge about the use, management of drugs stores, obtains, and disposes of drugs. Public Health Counseling activities are carried out using counseling methods. There is a progression from planning to enactment to assessment in this endeavor. Educational activities are delivered with related material displayed using power points. Public Health Counseling activities that have been carried out at MAS Al-Manar Medan Johor to students majoring in science are effective in increasing knowledge about pharmacist professional fields and introduction to DAGUSIBU medicine can also increase students' knowledge about how to get medicine, classification of drugs, how to safely keep narcotics and how to safely dispose of them, both of which have implications for the community at large.